KONSEP ETIKA PRODUKSI MENURUT PEMIKIRAN MUHAMMAD NEJATULLAH SIDDIQI - Mega Silvia; Yadi Janwari; Ayi Yunus Rusyana (GoAcademica Research dan Publishing, 2022)
The ethics of production is the most important element in a process or in an economic system, because in production it is regulated how the use of production ethics and what can be produced in order to be utilized by humans in meeting their needs, a very big problem felt by Muslims today when faced with a contemporary economic system that is free of value, namely capitalist and socialist economic systems. The purpose of writing this article is to find out how Muhammad Nejatullah Siddiqi thought about the ethics of production and how the factors of production according to Muhammad Nejatullah Siddiqi. The research method used by the author is a library research method with a qualitative approach that is a technique of collecting data from books, journals, articles and the internet related to the problems studied. The results stated that Muhammad Nejatullah Siddiqi's thoughts can be understood justice in production that is to put the value of justice by producing and utilizing goods in a circle that is halal to the needs of humans, because in this way they improve the standard of living and obtain wealth.